PERAN ORANG TUA DALAM MENINGKATKAN MOTIVASI BELAJAR ANAK DI RA AL IRSYAD KARANGPLOSO MALANG (UNISMA, 2020)
Children's learning motivation is a passion or encouragement obtained by children in learning activities to achieve a certain goal. The study was conducted at RA Al Irsyad Karangploso Malang. It is known that, children have different learning motivations. This is influenced by the role of parents in providing motivation to learn to their children, because each parent has a different way to improve children's learning motivation. The role of parents is very important especially in early childhood education, because at this time the child is in a critical or golden period. So parents must be able to develop various aspects of child development well. In carrying out their role as parents in enhancing children's learning motivation, parents have different constraints including parent time with children, parental knowledge and parental emotions. Differences in each way or role and the constraints of parents, each child must still get enough motivation from the people around him, especially parents. So that children can grow and develop in accordance with the expected goals.